Emergent craniotomy in rural and regional settings: recommendations from a tertiary neurosurgery unit: diagnosis and surgical decision‐making. Issue 7 (17th June 2022) - Raman, Vignesh; Jiwrajka, Manasi; Pollard, Cliff; Grieve, David A.; Alexander, Hamish; Redmond, Michael
Abstract: Largely attributed to the tyranny of distance, timely transfer of patients with major traumatic brain injuries (TBI) from rural or regional hospitals to metropolitan trauma centres is not always feasible. This has warranted emergent craniotomies to be undertaken by non‐neurosurgeons at their local hospitals with previous acceptable results reported in regional Australia. Our institution endorses this ongoing potentially life‐saving practice when necessary and emphasize the need for neurosurgical units to provide ongoing TBI education to peripheral hospitals. In this first of a two‐part narrative review, the authors describe the recommended diagnostic pathway for patients with a suspected TBI presenting to rural or regional hospitals and discuss local surgical management options in the presence or absence of a CT scanner. Abstract : Emergent trauma craniotomies may need to be performed in rural and regional hospitals if patients are unable to be transferred to metropolitan trauma centres in a timely fashion. We explain how to select the correct patients for intervention.